Back Matter JGI Des 2015 - Indonesia, Jurnal Gizi (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2015)
Author Guidelines; Reviewer Acknowledgement; Subjectand Author Indexes; Subscription form;Â dan Back Cover